Fracasso escolar na classe média: o inesperado em questão - Rodrigo Antonio Simoes da Silva Pena (2014)
The aim of this study was to better understand the educational trajectories of students from middle-class, even with the two characteristics mentioned by Bourdieu (1964, 1970 etc.) as the most positively impactful for school careers, namely, whether it comes from Economic Capital owning families, and especially the Cultural Capital, still, opposed all family, school, social and sociological expectations, are in a situation of school failure. Analyzed from a qualitative methodological approach, four cases. Three students and a student, everyone attending high school. We conducted 12 interviews, 3 in each case - one with the mother, other with a teacher and more one with the student - and, through them, we built "sociological profiles" that we use in interpreting the data obtained. We conclude, in the end, a number of points that must be taken into account in explaining the educational trajectories studied, being prominent type of relationship the family has with the education of the children, the fact that individual effort is central to trajectories of academic success in middle class, otherwise, there are great chances of failure, and the type of relationship that the student and his family have to learn and the school. Furthermore, we understand that the school performance does not affect the disposition of the middle class for the arrival of children to higher education and, also, that this predisposition to invest intensely in school, makes these families suffer, too intensely, with tensions and anxieties derived from the relationship between educational outcomes and high expectations. Finally, we question the impact of the teaching profession for the education of the children and the discourse of parental failure, concluding that parental absence, in these cases, is a half-truth.